A politeness strategy in expressing sympathy by American and Vietnamese speakers. - Tạ, Thị Thanh Hiền (University of Languages and International Studies, 2017)
This study investigates the politeness strategies employed by American and Vietnamese native speakers expressing sympathy. It attempts to seek what politeness strategies Vietnamese and American speakers use in expressing sympathy, and then how Vietnamese teachers and learners should acquire politeness strategy. The data was analyzed using a Discourse Completion Test (DCT) and basing on the models proposed by Blum-Kulka, et al (1989) including three dimensions: the Head Act, the Internal modifications and External modifications.